Correlation of FISH and PRAME Immunohistochemistry in Ambiguous Superficial Cutaneous Melanocytic Proliferations. (December 2021) - Harvey, Nathan T.; Peverall, Joanne; Acott, Nathan; Mesbah Ardakani, Nima; Leecy, Tamazin N.; Iacobelli, Jean; McCallum, Dugald; Van Vliet, Chris; Wood, Benjamin A.
Abstract : Abstract: Preferentially expressed antigen in melanoma (PRAME) is a tumor-associated repressor of retinoic acid signaling which is expressed in melanoma and has emerged as a potential biomarker for malignant behavior in melanocytic neoplasms. Although ancillary molecular techniques such as fluorescence in situ hybridization (FISH) are established techniques in the diagnosis of problematic cutaneous melanocytic proliferations, they are expensive, time-consuming, and require appropriate infrastructure, which places them out of reach of some laboratories. The advent of readily available commercial antibodies to PRAME has the potential to provide a more accessible alternative. The aim of this study was to determine whether immunohistochemistry for PRAME could serve as a surrogate for FISH analysis in a subgroup of challenging superficial melanocytic proliferations. Cases which had previously been submitted for FISH analysis were stained for PRAME and interpreted by a panel of at least 3 dermatopathologists is a blinded fashion. Of a study set of 55 cases, 42 (76%) showed a pattern of PRAME immunostaining which was concordant with the cytogenetic interpretation, with an unweighted kappa of 0.42 (representing mild-to-moderate agreement). Thus, although there was a correlation between positive immunohistochemistry for PRAME and abnormal findings on FISH analysis, in our view, the concordance was not sufficient to enable PRAME immunohistochemistry to act as a surrogate for FISH testing. Our findings reiterate the principle that interpretation of problematic superficial melanocytic proliferations requires a synthesis of all the available data, including clinical scenario, morphological features, immunohistochemistry, and ancillary molecular investigations.